2018
DOI: 10.1016/j.amepre.2018.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Providers’ Prediabetes Screening, Testing, and Referral Behaviors

Abstract: This study highlights the importance of increasing primary care provider awareness of and referrals to the CDC-recognized lifestyle change program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 29 publications
0
49
1
1
Order By: Relevance
“…Our respondents' DPP awareness was similar to that reported in the 2016 national survey of primary care physicians. 20 Low DPP awareness may be due to the relatively recent rollout of the National DPP and scale-up of organizations offering the DPP. Community organizations or local health departments may host DPPs, and clinicians may have limited awareness of community-based patient resources.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our respondents' DPP awareness was similar to that reported in the 2016 national survey of primary care physicians. 20 Low DPP awareness may be due to the relatively recent rollout of the National DPP and scale-up of organizations offering the DPP. Community organizations or local health departments may host DPPs, and clinicians may have limited awareness of community-based patient resources.…”
Section: Discussionmentioning
confidence: 99%
“…About two thirds of clinicians indicated that they referred 25% to 50% of their patients with prediabetes which is similar to the 23% of primary care clinicians who reported making a DPP referral in the 2016 national survey. 20 At the time of the EHR review, an electronic DPP referral did not exist and there was no process for referring patients to the 2 local DPPs. Some clinicians may have discussed DPPs with patients: however, this was not captured as part of our EHR review.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Those with elevated risk scores are advised to contact their healthcare provider for a diabetes screening test and/or enroll in an evidencebased diabetes prevention program. Although the uptake of these risk scores in community settings is unknown, their use in clinical practice is low [39]. This may, in part, reflect challenges of automating these tools within electronic health records (EHRs) due to risk factors that are not systematically captured in structured data fields (e.g., physical activity) [40].…”
Section: Diabetes Risk Assessment: Identifying High-risk Individuals mentioning
confidence: 99%